Inhibition of Clot Retraction by Previous In Vitro Platelet Aggregation - de Gaetano, G; Donati, M. B; Vermylen, J; Verstraete, M (Thrombosis and Haemostasis, 1971)
Clot retraction was not observed in plasma when coagulation was preceded by in vitro platelet aggregation; this inhibition was proportional to the degree of platelet aggregation.In the absence of continuous stirring, the coagulation of citrated-platelet rich plasma by CaCl2 was not preceded by measurable aggregation of platelets and was followed by normal retraction of the clot. In presence of a continuous stirring of platelet-rich plasma, the addition of CaCl2 led to platelet clumping and coagulation but not to clot retraction.Platelet-rich plasma containing ADP-unresponsive platelets, retracted normally.Using different inhibitors of platelet aggregation, clot retraction was shown to be inhibited by antimycin A and by 2-deoxy-D-glucose together, but was normal in presence of adenosine or acetylsalieylic acid.Which pool of ATP provides energy for clot retraction has been discussed.Suggestions were presented that the appearance of platelet factor 3 activity during clotting is not invariably linked to platelet aggregation.